Foundry Dust - Alternative Additive for Green Sand Mixtures - Kielar, Š.; Weider, M.; Szucki, M.; Bašistová, M.; Bašistová, M.; Lichy, P. (Archives of Foundry Engineering, 2026)
Foundry dust is a significant component of the waste produced by the foundry industry worldwide. This waste is generated during mould making, melting, casting and discharging of moulds, where dust particles are released and subsequently captured by filters. Like most foundry waste, foundry dust usually ends up in landfills. However, this method of waste management faces problems related to environmental and economic requirements, especially in view of tightening legislation. It is important to point out that foundry dust contains components that could be reused in the production of foundry mixtures. The aim of this study is to evaluate the possible positive and negative effects of two foundry dust samples on the quality of the green sand mixtures. Basic analyses include the chemical composition of the leachate in aqueous solution and the granulometric composition of the dust particles. Furthermore, the properties of other ingredients for the preparation of green sand mixtures will be characterized. The study serves as a starting point for future research in the reuse of foundry dust in green sand mixtures, thus contributing to the sustainability of industrial processes.